Convalescence. Some comments about COVID-19 - Alfredo Darío Espinosa Brito; Alfredo Alberto Espinosa Roca (Medisur)
Convalescence is the last stage of the "natural history of a disease" - if death does not occur - and it is often not given full attention, so it is not idle to review some of its basic concepts. One year after the onset of the unprecedented SARS-CoV-2 pandemic, the gaze has turned to this evolutionary stage of the patients and to the identification and monitoring of clinical manifestations and possible effect. With the purpose of deepening the importance of this stage in COVID-19 patients and specifying its main characteristics, this work was carried out to contribute to its better understanding with updated information and favor the results in its management. The concepts of clinical discharge and epidemiological discharge and the need to assess the previous diagnosis are addressed. It insists on the factors that can influence convalescence: the characteristics of each person (biological, psychological, social, cultural and spiritual); the "state of seriousness" that the patient had in the acute phase of the disease and whether there was a need for admission to intensive care; adverse effects of medications and other procedures carried out during care and comorbidities.